Performance Levels and Perspective of Graduate Learners’ on Fully Online Learning During Covid-19 - Jaspal Kaur A/P Naranjan Singh; Safiah Md Yusof; Raziana Che Aziz; Siti Aishah Hashim Ali (2021)
Open University Malaysia (OUM) is a leading open and distance learning institution in Malaysia that offers its programs in blended mode. The blended mode of learning comprises self-managed learning, face-to-face tutorials, and online forum. Through its learning platform, named ‘myINSPIRE’, OUM has successfully offered some of its programmes fully online. The outbreak COVID-19 in early 2020 has pushed OUM to offer all its programmes fully online, including programmes for graduates. Measures were taken to improve teaching and learning support online. Part of the efforts included having weekly e-lessons and e-tutorials, as well as online exams. Learners have been exposed to new learning experiences where they faced many challenges. This study is conducted with the aim to investigate how these changes have affected learners’ performance and their perspective towards fully online learning. A total of 143 post graduate learners enrolled in OUM under the Cluster of Applied Sciences participated in this study. The readiness for change model used in the study is based on Technology Acceptance Model (TAM). The model applies perceived usefulness and perceived ease of use to measure user acceptance of technology. The findings indicate that overall, the graduate learners have an acceptable level of readiness for change and are able to adapt and continue learning online despite facing some issues and challenges. It was found that the performance of the learners pre- and post- lockdown seemed to be comparable. Nevertheless, there is a need to find ways to improve and better tailor the online learning environment for our adult learners so as to make their fully online learning experience more rewarding.